System for recognition of optical tools,based on fractal mathematic views - Kurskoy, Yu. S.; Hnatenko, O. S. (My University, 2021)
The aim of the paper is to create a fractal model for detection and recognition of optical systems. The model is based on fractal insights about the structure of the optical signal and determination of the fractal dimension intensity distribution in a cross-sectional plane of the laser pulse reflected from the target. It is shown that the approximation of the fractal di-mension value to unity is a prerequisite to the target classification as an optical surveillance device. In order to classify the type of an optical device along with the fractal dimension the group of the fractal characteristics, consisting of the type of fractal signatures, the type of spatial spectrum and the values of spatial frequency that characterize the signal structure must be developed.
Keywords: optical system; laseer; optical signal; fractals